2017
DOI: 10.1016/j.tjog.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Managing vulvovaginal hematoma by arterial embolization as first-line hemostatic therapy

Abstract: We successfully managed two cases of puerperal vulvovaginal hematoma by arterial embolization based on the evaluation of an enhanced CT scan. In conclusion, we suggest arterial embolization to be a viable option for first-line treatment in the management of vulvovaginal hematomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Takagi et al . also reported TAE as a first‐line hemostatic therapy, followed by removal of the hematoma and re‐suturing . Dahdouh et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Takagi et al . also reported TAE as a first‐line hemostatic therapy, followed by removal of the hematoma and re‐suturing . Dahdouh et al .…”
Section: Discussionmentioning
confidence: 98%
“…1 Takagi et al also reported TAE as a first-line hemostatic therapy, followed by removal of the hematoma and re-suturing. 10 with upper vaginal wall hematomas that formed in the supralevator space required TAE; therefore, TAE might be the first choice of treatment for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The supravaginal or subperitoneal type is clinically occult despite significant blood loss, and a high index of suspicion is required to diagnose and manage these hematomas promptly before signs of cardiovascular collapse develop (Mawhinney and Holman 2007). Effective management strategies have been reported for PGHA, including CM (Propst and Thorp 1998;Palmer and Knudstson 2008), SURG (Abbott et al 1965;Heffner et al 1985;Zahn et al 1996), a balloon tamponade device (Ghirardini et al 2012), and AEM (Hsu and Wan 1998;Villella et al 2001;Distefano et al 2013;Baruch et al 2015;Takagi et al 2017); but many of these have been described only in case reports. In deciding the treatment modality, it is necessary to identify the most reliable clinical findings; however, no prospective clinical trials or retrospective studies have been conducted in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…AEM has been reported as a reliable therapeutic option for PPH, especially for cases of PGHA in which hemostasis cannot be achieved by CM or SURG (Hsu and Wan 1998;Pelage et al 1998;Villella et al 2001;Banovac et al 2007;Baruch et al 2015;Soyer et al 2015;Koganemaru et al 2016; Committee on Practice Bulletins-Obstetrics 2017; Lee et al 2018). Moreover, the efficacy of AEM as the initial treatment for PGHA has recently been reported (Distefano et al 2013;Takagi et al 2017). Although these studies emphasized the high reliability of AEM regarding identification of the bleeding vessels and the high hemostasis success rate (Hsu and Wan 1998;Villella et al 2001;Distefano et al 2013;Baruch et al 2015;Takagi et al 2017), most of these articles are case reports that did not record the specific critical indications for AEM as the initial treatment for PGHA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation